The discretion of the judge on personal status issues in Iraqi law - Yousif ganim thageel alzeadi; Dr. Muthanna Court of Resume (Journal of College of Education, 2026)
This research addresses a very important topic: the judge's discretionary power in personal status court matters. Given the direct contact and interaction these procedures have with family formation, the legislator must give this topic a special character. Texts and laws have been adopted to legislate provisions specific to personal status matters, including marriage and divorce.These issues relate to Islamic legal rulings. Therefore, this research attempts to answer a key question: What is the extent of the judge's authority before the Personal Status Court under Iraqi law? It adopts a descriptive approach, presenting and interpreting legal texts and the opinions of jurists, and clarifying the positions of the Iraqi Civil Procedure Code and Personal Status Law.At the end of the research, we reached several conclusions, including that Iraqi law refers to the issue of dissolution and sanctity in marriage and divorce cases. Finally, several recommendations were made
Keywords: power, discretion, judge, personal status, law, Iraqi